Designing mobile based computational support for low-literate community health workers. Issue 115 (July 2018) - Shah, Hirav; Sengupta, Amit
Highlights: Rural women can use mobile technology with color coded interface along with voice annotation in local language. Rural women can easily adapt touch screen interface. Literate rural women were unable to use Hindi keypad on smart phones. "Rangoli" concept along with nine dots pattern lock technique used to design a unique interface for digital signature. Abstract: Now days, mobile phones provide major computational support in many areas such as healthcare, education, financial and many more but the major issue is usability for illiterate, semi-literate and novice users. This article describes the design process of user interface (UI) development for low-literate and novice Community Health Workers (CHWs) to provide computational support for their major activity related to maternal healthcare in rural India. To understand what kind of mobile functionality they can use and how they have adopted it, a contextual inquiry based design process was followed. Based on the design process, two main activity UIs was developed and tested, one for data collection and information dissemination and second for digital signature for data authentication. In context of text-free interface, color-coded graphical interface along with pre-recorded voice instructions in local language was used to develop first activity while Indian traditional art based "Rangoli" concept along with nine dots pattern lock technique was used to design a unique interface for digital signature for second activity. This study was conducted in tribal area of Bastar district of Chhattissgarh, India. To understand mobile usability, 97 low-literate and novice users were selected and for testing of UI design 18 subjects for first activity and 24 subjects for second activity were selected from the same area. Our initial results show that the task completion with both the activities was high with very few errors. With pre-recorded voice instructions in various languages, the same application platform with color-coded graphical UI can be used effectively in countries like India where many regional languages are there. And digital signature interface can provide authentication mechanism and reduce issues related to fake data entries by community health workers (CHWs).